Strategies For 2-Heptanone Biosynthesis From Octanoic Acid By Penicillium Roqueforti Spores - M Arpah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
This paper reviews two strategies of 2-heptanone (blue cheese aroma compound) biosynthesis from octanoic acid by Penicillium roqueforti spores. First, the production and preparation of fungal spores are discussed a long with effect of spores treatment on their biocatalytic activity. Following this the first strategy of 2-heptanone production i.e batch production of 2-heptanone by submerged bioconversion process is discussed. Furthermore 2-heptanone loss by air stream stripping due to its hight volatility is evaluated and then the second strategy, that is continuous biosynthesis in aerated stirred reactor, is addressed. An option for controlling pH of biosynthesis medium is also discussed. Finally, in the concluding paragraphs, utility of the strategies are presented. Key words: Spore, penicillium roqueforti, 2-heptanone.